Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Pendidikan Agama Islam Mengunakan Media di Kelas V UPTD SD Negeri 03 Harau - Dian Nuraga; Syawaluddin Syawaluddin; Deslita Deslita; Refi Fitria; Maisal Hayani; Amiruddin Amiruddin (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the low learning outcomes of Islamic Religious Education students in Class V UPTD SD Negeri 03 Harau. By using audiovisual media in learning will greatly help students' understanding. The purpose of this study is to: determine the increase in Islamic Religious Education (PAI) learning outcomes of students through media in class V UPTD SD Negeri 03 Harau. Data collection techniques used are tests and observations. The results of the study indicate that media in PAI subjects elemen fiqih can increase students' learning motivation, especially class IV students of UPTD V UPTD SD Negeri 03 Harau. Quantitative evidence can be seen from the increase in the motivation variable test from the first meeting and the second meeting. From the test results, there was also an increase from the pre-action results of 45%, in cycle I (first) it increased to 60%, in cycle II (second) it also increased to 90%. While qualitative evidence can be explained from the number of students who expressed their pleasure in the use of this audiovisual media, the growth of motivation, student concentration on PAI subjects.